The hydrodynamic limit of a deterministic particle system with conservation of mass and momentum - Mürmann, Michael (Journal of statistical physics, 2001)
We study the hydrodynamic limit of a deterministic one-dimensional particle system with nearest neighbour interaction and an additional regularizing force. Under its evolution mass and momentum are conserved. In the limit with Euler scaling their macroscopic distributions are shown to be governed by the compressible Navier-Stokes equations with a density dependent viscosity.